A case of early small bowel obstruction after total abdominal hysterectomy: A rare case (Indian Journal of Case Reports, 2020)
Hysterectomies are one of the foremost commonly performed operations. The formation of adhesions may be a well-known complication of hysterectomy. We present a case of adhesion-related small bowel obstruction (SBO) occurring within 1 week of a total abdominal hysterectomy and bilateral salpingo-oophorectomy. The patient underwent exploratory laparotomy. Intraoperative findings showed drainage of 100 mL serous fluid and dilated jejunal and ileal loops with adhesions of the terminal ileum with the vaginal vault. Careful surgical technique measures and also the use of anti-adhesive agents wherever appropriate should be taken. It is, therefore, important to always consider the complication of adhesion-related SBO following surgery, no matter how short the period of time is.